2017
DOI: 10.1111/jvim.14666
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Probiotic‐Prebiotic Supplement on Incidence of Diarrhea in a Dog Shelter: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: BackgroundDiarrhea is the most frequent morbidity affecting kenneled dogs in animal shelters. Diarrhea impacts animal welfare and the finances of the shelter as they must treat, clean, and house affected animals until recovered.Hypothesis/ObjectivesSupplementing dogs entering an animal shelter with a probiotic‐prebiotic, known as a synbiotic, will decrease the incidence of diarrhea.AnimalsSeven hundred and seventy‐three dogs entering an animal shelter in the United Kingdom.MethodsA prospective double‐blind, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 12 publications
0
49
1
1
Order By: Relevance
“…A previous study for instance showed varying microbial changes in kenneled dogs depending on the dosage of the probiotic treatment [ 17 ]. Several studies showed an improvement in clinical signs by probiotic treatment such as causing significant decreased incidence of diarrhea in sheltered dogs and a significant reduction in duration of uncomplicated acute diarrhea in dogs [ 18 – 20 ]. Dogs with idiopathic inflammatory bowel disease treated with probiotics in addition to standard therapy showed an enhancement of regulatory T-cell markers, normalization of dysbiosis, and up-regulated expression of tight junction proteins [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study for instance showed varying microbial changes in kenneled dogs depending on the dosage of the probiotic treatment [ 17 ]. Several studies showed an improvement in clinical signs by probiotic treatment such as causing significant decreased incidence of diarrhea in sheltered dogs and a significant reduction in duration of uncomplicated acute diarrhea in dogs [ 18 – 20 ]. Dogs with idiopathic inflammatory bowel disease treated with probiotics in addition to standard therapy showed an enhancement of regulatory T-cell markers, normalization of dysbiosis, and up-regulated expression of tight junction proteins [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given these premises, to maintain the correct equilibrium in the GI microbiota, human and animal medicine have increased the use of prebiotic, probiotic or synbiotic (the combination of the two) and faecal microbiota transplantation (FMT) (Rose et al 2017;Pilla and Suchodolski 2019;Whittemore et al 2019). The higher short chain fatty acids production due to an increasing fermentation activity in large intestine of dogs (Musco et al 2018) and cats (Calabr o et al 2020), affects energy balance (Deng and Swanson 2015;Fluitman et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These dogs did not have reported clinical symptoms of GI diseases, so the clinical impact of this change by SN is unknown. It is intriguing to speculate that the presence of these pathogens may indicate increased susceptibility or predisposition to developing GI disorders or diseases, and that SN treatment may have a prophylactic effect by reducing their abundances as previously reported [60][61][62] . Consistent with this was our finding that the PL group had a non-significant trend toward higher incidence of diarrhea than SN.…”
Section: Discussionmentioning
confidence: 87%